2017
DOI: 10.1016/j.neuroscience.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of single corrective steps evoked in the standing rabbit

Abstract: Single steps in different directions are often used for postural corrections. However, our knowledge about the neural mechanisms underlying their generation is scarce. This study was aimed to characterize the corrective steps generated in response to disturbances of the basic body configuration caused by forward, backward or outward displacement of the hindlimb, as well as to reveal location in the CNS of the corrective step generating mechanisms. Video recording of the motor response to translation of the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Recently, subpopulations of vestibular nuclei neurons in the cat have been shown to alter their firing in response to extension, flexion, or unidirectional movements of the hindlimb (McCall et al, 2016). Given the importance of somatosensory information for postural control (Karayannidou et al, 2009;Hsu et al, 2017), it seems likely that the LVN serves to integrate multiple modalities of sensory information concerning body and limb position and movement, with activation of a select set of these inputs recruiting a subpopulation of LVN neurons to appropriately modify spinal motor programs.…”
Section: Temporal Segregation Of Lvn Outputmentioning
confidence: 99%
“…Recently, subpopulations of vestibular nuclei neurons in the cat have been shown to alter their firing in response to extension, flexion, or unidirectional movements of the hindlimb (McCall et al, 2016). Given the importance of somatosensory information for postural control (Karayannidou et al, 2009;Hsu et al, 2017), it seems likely that the LVN serves to integrate multiple modalities of sensory information concerning body and limb position and movement, with activation of a select set of these inputs recruiting a subpopulation of LVN neurons to appropriately modify spinal motor programs.…”
Section: Temporal Segregation Of Lvn Outputmentioning
confidence: 99%
“…Reactive balance responses are composed of three phases mediated by a distributed and complex neural network: 1) short-latency (SL) < 80 ms, 2) medium-latency (ML) 80-120 ms, and 3) long-latency (LL) > 120 ms (Jacobs & Horak, 2007). The earliest phases of the responses involve spinal (Fung & Macpherson, 1999; Macpherson et al, 1997) and subcortical structures (Honeycutt & Nichols, 2010;Hsu et al, 2017;Stapley & Drew, 2009), with cortical regions exerting more signi cant in uence as the balance responses progress (Adkin et al, 2006;Dietz et al, 1985;Dimitrov et al, 1996;Ghosn et al, 2020;Marlin et al, 2014;Palmer et al, 2021; Payne & Ting, 2020). Although little work has assessed the neural underpinnings of reactive balance in PwPD, a recent connectivity study associated the subcortical and cerebellar networks with reactive balance in PwPD (Ragothaman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Backward and sideways locomotion are usually generated in the context of avoidance behavior. In addition, single steps in different directions are generated for postural corrections to restore balance or the basic body configuration perturbed during standing (Beloozerova et al, 2003;Karayannidou et al, 2009;Hsu et al, 2017) and FW locomotion (Musienko et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The latter includes networks generating the horizontal component of the step in different directions. It was also suggested that the same mechanisms generate a single corrective step in a particular direction in response to sensory information signaling a distortion of balance or body configuration (Hsu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%